HIV-1-Infected and Immune-Activated Macrophages Induce Astrocytic Differentiation of Human Cortical Neural Progenitor Cells via the STAT3 Pathway - Peng, Hui (Public Library of Science, 2011)
Diminished adult neurogenesis is considered a potential mechanism in the pathogenesis of HIV-1-associated dementia (HAD). In HAD, HIV-1-infected and immune-activated brain mononuclear phagocytes (MP; perivascular macrophages and microglia) drive central nervous system (CNS) inflammation and may alter normal neurogenesis. We previously demonstrated HIV-1-infected and lipopolysaccharide (LPS) activated monocyte-derived macrophages (MDM) inhibit human neural progenitor cell (NPC) neurogenesis, while enhancing astrogliogenesis through the secretion of the inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), in vitro and in vivo. Here we further test the hypothesis that HIV-1-infected/activated MDM promote NPC astrogliogenesis via activation of the transcription factor signal transducer and activator of transcription 3 (STAT3), a critical factor for astrogliogenesis. Our results show that LPS-activated MDM-conditioned medium (LPS-MCM) and HIV-infected/LPS-activated MDM-conditioned medium (LPS+HIV-MCM) induced Janus kinase 1 (Jak1) and STAT3 activation. Induction of the Jak-STAT3 activation correlated with increased glia fibrillary acidic protein (GFAP) expression, demonstrating an induction of astrogliogenesis. Moreover, STAT3-targeting siRNA (siSTAT3) decreased MCM-induced STAT3 activation and NPC astrogliogenesis. Furthermore, inflammatory cytokines (including IL-6, IL-1β and TNF-α) produced by LPS-activated and/or HIV-1-infected MDM may contribute to MCM-induced STAT3 activation and astrocytic differentiation. These observations were confirmed in severe combined immunodeficient (SCID) mice with HIV-1 encephalitis (HIVE). In HIVE mice, siRNA control (without target sequence, sicon) pre-transfected NPCs injected with HIV-1-infected MDM showed more astrocytic differentiation and less neuronal differentiation of NPCs as compared to NPC injection alone. siSTAT3 abrogated HIV-1-infected MDM-induced astrogliogenesis of injected NPCs. Collectively, these observations demonstrate that HIV-1-infected/activated MDM induces NPC astrogliogenesis through the STAT3 pathway. This study generates important data elucidating the role of brain inflammation in neurogenesis and may provide insight into new therapeutic strategies for HAD.